Kinetic, phase equilibrium, and simulation studies of base-catalyzed coconut oil transesterification with methanol - Subosa, Bemboy Nino F.; Munoz, Jose C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The mandated increase of coconut biodiesel blend to 10% by 2020 by the Biofuels Act of 2006 will increase the local biodiesel demand. Adequate physicochemical data should be available for an effective and efficient design, operation, and control of the production process that will provide this demand. The process involves the transesterification of coconut oil with methanol to produce fatty acid methyl ester (FAME, also known as coco methyl ester or CME) and glycerol, and the separation and purification of biodiesel from excess methanol and glycerol. The kinetics of the transesterification reaction and liquid-liquid equilibrium behavior of biodiesel, methanol, and glycerol mixtures were investigated in this study. A pseudo-first order fit adequately described the forward reaction, while a second-order fit was found satisfactory for the reverse reaction. The vant Hoff plot of the equilibrium constant with temperature confirmed the observed exothermicity of the reaction, with the equilibrium conversion decreasing with increasing temperature. The Non-Random Two-Liquid (NRTL) model for the determination of activity coefficients was found to provide a satisfactory description for the Type I liquid-liquid equilibrium behavior of two-phase mixtures of biodiesel, methanol, and glycerol. The Othmer-Tobias correlation was shown to be able to generate additional tie-lines from two experimental tie-line data. Distribution coefficient values indicated a greater affinity of methanol for the glycerol-rich phase than the biodiesel rich phase, implying lesser purification requirements for biodiesel. Reactor simulation studies revealed that the adiabatic continuous stirred-tank reactors arranged in series with interstage cooling provide better conversion values than a single, isothermal case
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman
Keywords: Coconut oil as fuel; Biodiesel fuels